Detailed clinical characterisation, unique features and natural history of autosomal recessive RDH12-associated retinal degeneration - Fahim, Abigail T; Bouzia, Zaina; Branham, Kari H; Kumaran, Neruban; Vargas, Mauricio E; Feathers, Kecia L; Perera, N Dayanthi; Young, Kelly; Khan, Naheed W; Heckenlively, John R; Webster, Andrew R; Pennesi, Mark E; et al. (British journal of ophthalmology, 2019)
BackgroundDefects in retinol dehydrogenase 12 (RDH12) account for 3.4%–10.5 % of Leber congenital amaurosis and early-onset severe retinal dystrophy (EOSRD) and are a potential target for gene therapy. Clinical trials in inherited retinal diseases have unique challenges, and natural history studies are critical to successful trial design. The purpose of this study was to characterise the natural history of RDH12-associated retinal degeneration.MethodsA retrospective chart review was performed in individuals with retinal degeneration and two likely disease-causing variants in RDH12.Results57 subjects were enrolled from nine countries. 33 subjects had clinical records available from childhood. The data revealed an EOSRD, with average age of onset of 4.1 years. Macular atrophy was a universal clinical finding in all subjects, as young as 2 years of age. Scotopic and photopic electroretinography (ERG) responses were markedly reduced in all subjects, and a non-recordable ERG was documented as young as 1 year of age. Assessment of visual acuity, visual field and optical coherence tomography revealed severe loss of function and structure in the majority of subjects after the age of 10 years. Widefield imaging in 23 subjects revealed a unique, variegated watercolour-like pattern of atrophy in 13 subjects and sparing of the peripapillary area in 18 subjects.ConclusionsThis study includes the largest collection of phenotypic data from children with RDH12-associated EOSRD and provides a comprehensive description of the timeline of vision loss in this severe, early-onset condition. These findings will help identify patients with RDH12-associated retinal degeneration and will inform future design of therapeutic trials.